Value-added tax : international practice and problems - Tait, Alan A. (Washington, D.C. : International Monetary Fund, 1988)
This books explores the different ways tax can be tailored and indicates some preferred solutions.
Includes index.
Bibliography: p. 417-432.
ucj 17/01/2019
Loans
Keywords: Value-added tax